Development and the use of coordinate measuring machines - Vasić, Siniša; Stankov, Jelena; Iskrin, Branko (Journal of Production Engineering, 1989)
Coordinate Measuring Machines (CMMs) represent one of the most contemporary metrology systems that enable the solution of all measuring tasks encountered in practice. This is possible due to their universality, flexibility, accuracy, and productivity. In the paper, a brief description of the historical development of CMMs, their classification, principles of operation, and their basic features is provided.